KONSTRUKSI DAN REPRESENTASI DISABILITAS PADA FILM MIRACLE IN CELL NO.7 VERSI INDONESIA - Rahayu Andira, Fifi; Malayati, Robi’ah Machtumah (Universitas Hasyim Asy'ari, 2024)
This study aims to analyze the construction of disability in the Indonesian version of the film Miracle in Cell No.7. The research employs an interpretive qualitative approach using John Fiske’s semiotic method. This approach is used to uncover the meaning of signs and codes that emerge through three levels: the level of reality, the level of representation, and the level of ideology, particularly in scenes portraying the main character, a father with intellectual disabilities. The results identify 16 scenes that construct the narrative of a disabled father’s sacrifice through visual elements, dialogue, and symbolism. However, the film also highlights the dilemma between promoting empathy for people with disabilities and reinforcing stereotypes of their helplessness. A critical perspective is encouraged in interpreting the film's representation, aiming for a more inclusive view of disability.